Human Assets and Management Dilemmas: Exploring the Importance of Measuring Human Assets in the Financial Sector (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The fundamental target of the investigation is to investigate current discernments and practices in the space of estimation of human asset zeroing in on the significance of estimating human asset distinguishing the obstructions for estimation of human asset recognizing current measures being utilized and considered to be utilized who ought to be liable for estimating it and impact of human asset valuation information on corporate share decisions of financial backers. To meet out these destinations, the factual treatment of the information got was completed from an example of 150 employees working in the service sector organizations. With the end goal of the examination, employee knowing about financial exchange tasks with some stake in at any rate one company in the financial exchange has been chosen to ensure that respondents are genuine parts in the securities exchange